2006
DOI: 10.1145/1151659.1159938
|View full text |Cite
|
Sign up to set email alerts
|

The impact and implications of the growth in residential user-to-user traffic

Abstract: It has been reported worldwide that peer-to-peer traffic is taking up a significant portion of backbone networks. In particular, it is prominent in Japan because of the high penetration rate of fiber-based broadband access. In this paper, we first report aggregated traffic measurements collected over 21 months from seven ISPs covering 42% of the Japanese backbone traffic. The backbone is dominated by symmetric residential traffic which increased 37%in 2005. We further investigate residential per-customer traff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(45 citation statements)
references
References 14 publications
0
43
0
2
Order By: Relevance
“…To model the user traffic demand, we refer to a study of residential broadband access networks in Japan [4]. That study found that the distribution of the amount downloaded by a user is heavy tailed.…”
Section: The Baseline Modelmentioning
confidence: 99%
“…To model the user traffic demand, we refer to a study of residential broadband access networks in Japan [4]. That study found that the distribution of the amount downloaded by a user is heavy tailed.…”
Section: The Baseline Modelmentioning
confidence: 99%
“…We assume that the ratio of P2P users among all users in each city is almost constant, and the number of users accommodated in lower network i is proportional to the population p i in the area for which the lower network i covers. In this case, we can assume that the ratio of requests generated by users accommodated in lower network i against the total requests in N lower networks is proportional to r i , which is the population covered by the lower network i divided by the total population among N lower networks [8]. In other words, r i is obtained by…”
Section: Assumptionsmentioning
confidence: 99%
“…Before evaluating each video streaming system, we investigate the effect of link weights on the network productivity in this section. Assuming the gravity model on r sd [6], i.e., setting r sd = p s p d , we compare h gv , the average hop length of flows, and V max,gv , the network productivity, when using min.hop and inv.cap. Fig.…”
Section: Effect Of Link Weights On Network Productivitymentioning
confidence: 99%